The role of German teachers’ community as a pioneer in improving teacher competence - Rudolf Kempa; Henderika Serpara; Lambertus Lokollo (Journal of Education and Learning (EduLearn), 2023)
The role of professional communities in improving teacher performance is crucial in this era. One such organization is the German language teachers’ community. This research aimed to describe two things: i) The role of the German language teacher community as a pioneer of the teacher community; and ii) The role of teachers as learning leaders in planning, implementing, and evaluating German language learning. The qualitative approach was used in this study. Furthermore, the research subjects were the head of the German language teachers’ community and German language teachers in Ambon City, Indonesia as members. Researchers collected data through observation, interviews, and documentation studies and analyzed the data following an interactive analysis model with analysis steps including data reduction, presentation, and verification. The results in this study showed that: i) The German language teacher community generally designs programs to strengthen teacher capacity through workshops, seminars, exchanging experiences, and making learning tools; ii) These programs are carried out according to a mutually agreed schedule by presenting competent resource persons; iii) The German language teacher community assists teachers in planning, implementing, and evaluating German language learning; and iv) As community members and learning leaders, teachers benefit from the above programs to independently practice the material they have learned at school. Implementing this role can be used as a role model for other communities.